Pengembangan Multimedia Interaktif Berbasis Augmented Reality Untuk Meningkatkan Penguasaan Konsep Pada Materi Ikatan Kimia - Dita Amalia; Nurlaili Nurlaili; Yuli Hartati (Universitas Pakuan, 2026)
DEVELOPMENT OF AUGMENTED REALITY-BASED INTERACTIVE MULTIMEDIA TO IMPROVE CONCEPT MASTERY IN CHEMICAL BONDING MATERIAL This study aimed to develop an Augmented Reality (AR)-based interactive multimedia application called Chembond AR to improve students' conceptual understanding of chemical bonding, particularly molecular geometry. The research was motivated by students' difficulties in visualizing abstract concepts, including Lewis structures, VSEPR theory, and molecular geometry. The study employed a Research and Development (R&D) approach using the ADDIE model consisting of Analysis, Design, Development, Implementation, and Evaluation stages. A needs analysis involving chemistry teachers and students of SMA Negeri 9 Balikpapan was conducted to determine product specifications. The multimedia application was developed using Unity 3D and Vuforia Engine for Android devices and incorporated three-dimensional molecular visualization, audio narration, interactive learning activities, and formative assessments. The developed product was validated by subject matter experts, media experts, and assessment instrument validators before being implemented with eleventh-grade students. Chembond AR is expected to facilitate meaningful learning by transforming abstract chemical concepts into concrete visual experiences, increasing student engagement, and supporting independent learning. Furthermore, the developed multimedia provides an innovative instructional medium aligned with the Merdeka Curriculum and twenty-first-century learning demands. Therefore, Chembond AR has strong potential to enhance chemistry learning quality and students' conceptual understanding through interactive, technology-supported, and visually enriched learning experiences. Students benefit from engaging exploration and improved scientific reasoning.